Appendicitis and COVID-19: yet another clinical dilemma - Saxena, Divish; Dubhashi, Siddharth P.; Kharkate, Ganesh (International Surgery Journal, 2020)
Acute appendicitis is the most common general surgery encountered in the emergency room worldwide. Management of acute appendicitis in patients who are tested positive for SARS-CoV-2 is still under debate as the full course of this novel disease is not yet mapped out. Here, we report three patients who presented with symptoms of acute appendicitis without any respiratory complaints. Three patients presented to surgical emergency room with classical symptoms and signs of acute appendicitis with modified Alvarado score of more than 6/9. Though they did not have any respiratory symptoms, they tested positive for SARS-CoV-2 by RT-PCR method. All patients underwent open appendicectomy. Open appendicectomy was preferred procedure to minimize aerosol generation and for safety of operating health care workers. Histopathology was suggestive of inflamed appendix and post-operative course was uneventful. Gastrointestinal symptoms like appendicitis could be a varied and sole presentation in patients suffering from COVID-19 infection. Conservative approach can be considered in all patients suffering from acute appendicitis and surgery can be reserved for those not responding to conservative line of management or having complications in form of perforated or gangrenous appendix and appendicular abscess. Further research may elaborate the correlation between COVID-19 and acute appendicitis.